2020
DOI: 10.1002/esp.4974
|View full text |Cite
|
Sign up to set email alerts
|

Variability in infragravity wave processes during estuary artificial entrance openings

Abstract: Intermittently open/closed estuaries (IOCE) are wave-dominated estuaries with entrances that temporarily close to the ocean. Wave-current interactions play a major role in estuary entrance morphodynamics and influence the degree of energy transfer from the ocean into the lagoon. This study utilizes artificial entrance openings of multiple ICOE in Victoria, Australia, to capture continuous hydrodynamic and geomorphic data throughout the opening cycle. We illustrate that water level oscillations in the infragrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Existing monitoring and survey techniques for coastal inlets include RTK-GPS and echo-sounding surveying (e.g., Mcsweeney and Stout (2020); Morris and Turner (2010)), stationary coastal imaging systems such as Argus (e.g., Harley et al (2011)) as well as more recent techniques such as UAVs (Turner et al, 2016) and airborne water penetrating LiDAR (Kinsela et al, 2020). While these techniques are suitable for surveying coastal inlets at a high resolution, they remain costly and their suitability for reconstructing historical inlet dynamics depends on when corresponding surveys were initiated.…”
Section: Existing Methods For Monitoring Coastal Inletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing monitoring and survey techniques for coastal inlets include RTK-GPS and echo-sounding surveying (e.g., Mcsweeney and Stout (2020); Morris and Turner (2010)), stationary coastal imaging systems such as Argus (e.g., Harley et al (2011)) as well as more recent techniques such as UAVs (Turner et al, 2016) and airborne water penetrating LiDAR (Kinsela et al, 2020). While these techniques are suitable for surveying coastal inlets at a high resolution, they remain costly and their suitability for reconstructing historical inlet dynamics depends on when corresponding surveys were initiated.…”
Section: Existing Methods For Monitoring Coastal Inletsmentioning
confidence: 99%
“…Information on the long-term spatial and temporal dynamics of coastal inlets would enable researchers to further advance the existing knowledge on the mechanics and drivers of inlet opening/closure (e.g., Behrens et al, 2013;Bertin and Mendes, 2019;GonzĂĄlez-Villanueva et al, 2017;Mcsweeney et al, 2018;Mcsweeney and Stout, 2020;Morris and Turner, 2010;Ranasinghe and Pattiaratchi, 2003;Slinger, 2017;van Ormondt et al, 2020;Velasquez Montoya et al, 2018), the hydrology (e.g., Gale et al, 2007) and ecology (e.g., Gladstone et al, 2006;Scanes et al, 2020) of intermittent estuaries, or the impacts of climate change on coastal inlet dynamics (e.g., Duong et al, 2016;Duong et al, 2017Duong et al, , 2018. To date, however, the potential of satellite remote sensing remains poorly explored and there is need for an automated and transferable method to monitor intermittent coastal inlets worldwide.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Recent work has focused on the influence of infragravity (IG hereafter) waves on sediment transport within tidal inlets (Dodet et al 2013;Bertin et al 2019Bertin et al , 2018. Multiple ICE observational studies and numerical simulations (XBeach) have shown that the strength of IG motions is correlated with offshore wave heights, and that the IG energy depends on the tidal phase and connectivity between the ocean and estuary (Williams and Stacey 2016;McSweeney et al 2020;Bertin and Olabarrieta 2016). Additionally, observations have found that the magnitude of IG orbital motions can be on the same order as tidal velocities (Uncles et al 2014;Williams and Stacey 2016;Bertin and Olabarrieta 2016).…”
Section: Communicated By Neil Kamal Ganjumentioning
confidence: 99%
“…Similarly, Bertin et al (2019) reported high currents during the passage of IG waves crests at a shallow tidal inlet, which resulted in an increase of the sand flux by at least two orders of magnitude that favored inlet closure. IG wave frequencies and amplitudes have been linked to variability in estuary entrance morphologies and offshore wave conditions (e.g., McSweeney et al, 2020;Williams & Stacey, 2016).…”
Section: 𝐿𝐿𝑁𝑁𝑁𝑁 = 𝑈𝑈mentioning
confidence: 99%
“…The effects of infragravity (hereafter IG) motions are not considered in the above formulations. Infragravity waves, while small offshore, have been shown to influence the hydrodynamics and morphodynamics of beaches, small tidal inlets and estuaries (Bertin et al., 2019; Bertin & Olabarrieta, 2016; Brocchini, 2020; Elgar et al., 1992; McSweeney et al., 2020; Melito et al., 2020; Mendes et al., 2020; Williams & Stacey, 2016). IG waves result in surface water level fluctuations with periods of 30–300 s that are typically associated with wave groups and result from nonlinear interactions in the incident short waves (Bertin et al., 2018; Henderson et al., 2006; SchĂ€ffer, 1993).…”
Section: Introductionmentioning
confidence: 99%